Distributional properties of the entropy transformed Weibull distribution and applications to various scientific fields - Tabassum Naz Sindhu; Anum Shafiq; Showkat Ahmad Lone; Qasem M. Al-Mdallal; Tahani A. Abushal (Scientific Reports)
Abstract A novel two-parameter continuous model titled the entropy-transformed Weibull (ET-W) distribution has been developed via the entropy transformation. A new framework has been investigated and found to meet the criteria of the probability function. By significantly improving the functional shape and having the ability to model the most likely form of the hazard rate function, this novel modification has increased the adaptability of typical model. Some of its core characteristics, such as its statistical and computational features, are simply and clearly presented. To examine the ultimate performance of maximum likelihood estimators during the process of estimating model parameters, a comprehensive simulation analysis has been conducted. The effectiveness of the suggested distribution is illustrated through the modeling of real datasets.